Pengaruh Akuntabilitas, Transparansi, Partisipasi Masyarakat terhadap Pengelolaan Dana Desa: Studi Kasus pada Pemerintah Desa Kecamatan Nasal Kabupaten Kaur Provinsi Bengkulu - Fitri , Alya; Indriani, Rini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was conducted to determine whether accountability, transparency and community participation have an influence on Village Fund Management in the Village Government of Nasal District 2023. The analysis tool in this research uses the help of the SmartPLS software program version 4.0 which consists of evaluating the outer model and inner model. This research is included in descriptive research and is clauseal. The population in this study is the Village Government of Nasal District. Sampling in this study used Nonprobability sampling technique with saturated sampling method so that 85 respondents were obtained from all village officials at the Nasal District Village Government. The results show that accountability has a significant effect in a positive direction on village fund management in the Village Government of Nasal District, Kaur Regency in 2023. Transparency has a significant effect in a positive direction on the management of village funds in the Village Government of Nasal District, Kaur Regency in 2023. Community participation has a significant effect in a positive direction on the management of village funds in the Village Government of Nasal District, Kaur Regency in 2023.